2022
DOI: 10.3389/fcell.2022.933852
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Visualization of Mouse Endometrial Remodeling After Superovulation

Abstract: Uterine status determines pregnancy success. Although it is well known that superovulation operations can disrupt uterine function, our understanding of the morphological changes in the uterine endometrium at the three-dimensional (3D) level is limited. Here, combining the tissue clearing with 3D deep imaging, we reveal an increase in epithelial density and angiogenesis after ovarian stimulation, which is accompanied by a circulating surge in P4 levels. Using an ovariectomized mouse model, we further detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It has been reported that superovulation in female mice leads to the expulsion of some low-quality oocytes [ 27 , 28 ] and produces an excessive number of embryos, which causes overload of the uterus [ 29 , 30 ] and impairment of fetal growth in utero [ 21 , 31 ]. The prenatal detrimental effects caused by superovulation in the mothers might increase the perinatal mortality of newborn mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that superovulation in female mice leads to the expulsion of some low-quality oocytes [ 27 , 28 ] and produces an excessive number of embryos, which causes overload of the uterus [ 29 , 30 ] and impairment of fetal growth in utero [ 21 , 31 ]. The prenatal detrimental effects caused by superovulation in the mothers might increase the perinatal mortality of newborn mice.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased VEGF expression in the ovaries was observed with the GnRHa trigger compared to the hCG trigger, which could explain the reduced ovarian hyperstimulation. Numerous research works have evaluated the ovarian, uterine, and fetal abnormalities caused by superovulation ( 18 20 ). Previous studies have shown that superovulation with the hCG trigger alters the expression of genes about tissue remodeling and placenta formation during implantation, resulting in abnormal placental and fetal growth ( 10 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that after the GnRHa trigger, the mouse uterus showed abnormal leukocyte distribution and higher inflammatory response ( 22 ). There are several studies showed that the use of HCG to trigger ovulation leads to impaired uterine receptivity ( 20 , 23 ). However, the effect of GnRHa-triggered protocols on embryo implantation has not been clarified, especially the ovarian and uterine changes in pre-implantation.…”
Section: Introductionmentioning
confidence: 99%